2012
DOI: 10.1155/2012/604141
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Measurements of theβ-Amyloid Pool in Blood Could Help in the Early Diagnosis of AD

Abstract: The present study was aimed at assessing the capability of Aβ1-40 and Aβ1-42 levels in undiluted plasma (UP), diluted plasma (DP), and cell bound (CB) to distinguish between early stages of Alzheimer's disease (AD), amnesic mild cognitive impairment (MCI), and healthy control (HC). Four blood samples from each participant were collected during one month and the levels of Aβ1-40 and Aβ1-42 were determined by a blinded proprietary ELISA sandwich (Araclon Biotech. Zaragoza, Spain). First striking result was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 52 publications
2
68
0
Order By: Relevance
“…Differences in blood sampling (fasting versus non fasting, time of the day, tube used for collecting blood) and storage protocols may account for a substantial portion of the observed heterogeneity [16]. Moreover, assays may differ in their capacity to capture Aβ peptides, and most of them can only detect free, circulating monomers, which represent less than 50% of all circulating Aβ peptides [39]. Finally, sample size, follow-up time and analysis strategies may also generate differences in association estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in blood sampling (fasting versus non fasting, time of the day, tube used for collecting blood) and storage protocols may account for a substantial portion of the observed heterogeneity [16]. Moreover, assays may differ in their capacity to capture Aβ peptides, and most of them can only detect free, circulating monomers, which represent less than 50% of all circulating Aβ peptides [39]. Finally, sample size, follow-up time and analysis strategies may also generate differences in association estimates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is a correlation between the affinity of peripherally-administered Ab-specific agents and the efflux of Ab from the brain to the serum [29]. As levels of Ab peptides in the blood are low (subnanomolar) [30][31][32][33][34], it is probably critical to use capturing-agents of high affinity for such applications.…”
Section: Biotechnology Journalmentioning
confidence: 99%
“…It has been shown that there is a correlation between the affinity of peripherally-administered Ab-specific agents and the efflux of Ab from the brain to the serum [29]. As levels of Ab peptides in the blood are low (subnanomolar) [30][31][32][33][34], it is probably critical to use capturing-agents of high affinity for such applications.It has previously been demonstrated that staphylococcal cell surface display in combination with fluorescenceactivated cell sorting (FACS) is well suited for combinatorial affinity maturation efforts, since it allows for high precision affinity discrimination between binders [35][36][37][38]. Recently, the method was used for affinity maturation of a HER3-specific Affibody, and generated binders with picomolar affinities [39].…”
mentioning
confidence: 99%
“…As Aβ is cleared from the brain, it can access extracellular fluids like cerebrospinal fluid (CSF) and blood [5], which would bring it in contact with plasma proteins. Since much of the Aβ produced in the brain is cleared through the cerebral vasculature, Aβ levels are higher in CNS venous blood compared to arterial blood [6] with some studies showing that elevated plasma Aβ levels are an early event in AD development [7, 8]. During clearance, Aβ can also accumulate around blood vessels as cerebral amyloid angiopathy (CAA).…”
Section: If Ad and Vascular Pathology Are Connected What Are The Mecmentioning
confidence: 99%